Zero Waste: Introduction to Pro-Environmental Behavior to Minimize Waste in the South Kalimantan Teaching and Trip Community - Firdha Yuserina; Sukma Noor Akbar; Meydisa Utami Tanau; Rahmiyati Rahmiyati (Lambung Mangkurat, 2022)
The Teaching and Trip Community is a community in the fields of education, literacy, and service. The problem is the inability to adapt to the pandemic situation so that community activities decline. Environmental issues in the form of high waste production and the characteristics of the community who want to follow the trend can be a momentum for the sustainability of the community. The community needs external parties to collaborate to run it. Therefore, researchers want to conduct zero waste training to improve pro-environmental behavior while driving community activities. The training consisted of providing material on community adaptation during a pandemic, pro-environmental behavior, and zero waste. The training consisted of 3 meetings with a duration of 100-120 minutes for each meeting. The success of this program will be measured quantitatively through comparison of pre-test and post-test scores and qualitatively through observation and interviews. The participants are 18 members of the community. Based on the comparison of pre-test and post-test results, 14 of 18 participants experienced an increase in their results. Participants experienced an increase in knowledge after being given training and became more aware of the concept and implementation of zero waste for the community and society.